DRAWING AND PLANTING UNITS DETERMINATION MODELS OF PRODUCTIVITY - M. Toshboltaev; B. Artikbaev (Galaxy International Interdisciplinary Research Journal, 2023)
The performance of machine and tractor units (MTU) is the most important indicator of their effectiveness. During field testing of new or modernized units, this indicator is taken as a criterion for assessing their performance. Consequently, conducting scientific research aimed at determining the composition and structure of analytical expressions for the performance of machine and tractor units is relevant. The purpose of this study is to develop mathematical models of the performance of units for chiseling and sowing seeds of agricultural crops. In the process of analytical research, well-known methods of analysis and synthesis of information, comparison of data and phenomena, and the scientific subject of operation of the machine and tractor fleet were used.